Population pharmacokinetics of tenofovir in HIV/HBV co-infected patients - Baralee Punyawudho (2018)
© 2015 Dustri-Verlag Dr. K. Feistle. Objective: Tenofovir is an efficacious drug with a long half-life and high activity against both HIV and HBV. However, the pharmacokinetics of tenofovir have not been studied in HIV/HBV co-infected patients. Data from HIV mono-infected patients may not be transferable to HIV/HBV co-infected population because the nature and consequences of the co-infection are different. This study developed a population pharmacokinetic model of tenofovir in patients with HIV/HBV co-infection and identified pathophysiologic factors that affect the pharmacokinetics of the drug. Methods: Sparse and intensive blood samples were collected from patients with HIV/HVB coinfection. The population pharmacokinetic model of tenofovir was developed by a nonlinear mixed-effects modeling approach (NONMEM®). Results: A total of 332 tenofovir plasma concentrations from 146 patients were obtained. A two-compartment model best described the pharmacokinetics of tenofovir. Creatinine clearance (estimated by Cockcroft and Gault equation) affected the tenofovir apparent clearance (CL/F). Tenofovir CL/F decreased by 23.5% when concomitantly used with atazanavir/ritonavir. Conclusions: Based on the results from our study, it was shown that the pharmacokinetics of tenofovir in HIV/HBV co-infected patients are comparable to those with HIVmonoinfection. This study confirmed that patients with kidney impairment and the concurrent use of atazanavir/ritonavir will require the dosage of tenofovir to be adjusted to ensure efficacy and prevent unwanted toxicities. The developed model can reliably be used to adjust for the dosage of tenofovir in this population, especially when therapeutic drug monitoring services are unavailable.